1996
DOI: 10.1084/jem.183.1.109
|View full text |Cite|
|
Sign up to set email alerts
|

Interleukin 4, but not interleukin 5 or eosinophils, is required in a murine model of acute airway hyperreactivity.

Abstract: SummaryReversible airway hyperreactivity underlies the pathophysiology of asthma, yet the precise mediators of the response remain unclear. Human studies have correlated aberrant activation of T helper (Th) 2-like effector systems in the airways with disease. A routine model of airway hyperreactivity in response to acetylcholine was established using mice immunized with ovalburain and challenged with aerosolized antigen. No airway hyperreactivity occurred in severe combined immunodeficient mice. Identically im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
477
6
7

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 700 publications
(525 citation statements)
references
References 52 publications
35
477
6
7
Order By: Relevance
“…Fig. 2 shows that the OVA-sensitized and challenged wild-type mice developed significant AHR compared with OVA-sensitized, PBS-challenged wild-type mice ( p Ͻ 0.05), consistent with other investigators (11,12). The baseline airway reactivities of OVA-sensitized and PBS-challenged IL-5 TG mice and similarly treated wild-type mice were nearly identical.…”
Section: Effects Of Airway Eosinophilia On Bronchial Reactivitysupporting
confidence: 86%
See 1 more Smart Citation
“…Fig. 2 shows that the OVA-sensitized and challenged wild-type mice developed significant AHR compared with OVA-sensitized, PBS-challenged wild-type mice ( p Ͻ 0.05), consistent with other investigators (11,12). The baseline airway reactivities of OVA-sensitized and PBS-challenged IL-5 TG mice and similarly treated wild-type mice were nearly identical.…”
Section: Effects Of Airway Eosinophilia On Bronchial Reactivitysupporting
confidence: 86%
“…In mice neutralization of IL-5 prevented allergen-induced AHR (9), and overproduction of IL-5 in the airways led to AHR (10). However, previous results, suggesting that AHR was prevented in IL-5 knockout mice (11), but was not prevented in mice treated with anti-IL-5 mAb, were conflicting (12). Furthermore, mice treated with anti-IL-5 mAb showed less eosinophilia, but retained their AHR (13,14).…”
Section: Marked Airway Eosinophilia Prevents Development Of Airwaymentioning
confidence: 92%
“…Presently, the participation of eosinophils in the development of AHR is not clear. Studies by Nagai et al (14) and Corry et al (43) showed that the anti-IL-5 Ab treatment inhibited airway eosinophilia, but not AHR. Kobayashi Wild-type and Fc⑀RI␣ Ϫ/Ϫ mice were sensitized to OVA in alum on days 1 and 14.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies indicate the existence of a mechanism dependent on IL-5 and eosinophils that induce pulmonary damage and intensify AHR [3][4][5]. In other studies, however, the induction of AHR was observed despite the absence of infiltrating eosinophils, suggesting dissociation between these phenomena [6][7][8][9][10]. Macrophage migration inhibitory factor (MIF) is a pleiotropic molecule and critical mediator of innate and acquired immune responses [11,12].…”
Section: Introductionmentioning
confidence: 99%